Cost-Effectiveness Analysis of a Three-Drug Regimen Containing Bevacizumab for the Treatment of Recurrent Pediatric Medulloblastoma in China: Based on a COG Randomized Phase II Screening Trial - Chen, Zhaoyan; Tian, Fangyuan; Chen, Xi (Frontiers in Public Health, 2022)
Background: Medulloblastoma is the most common malignant brain tumor of childhood, accounting for 6 to 7 percent of all childhood CNS tumors. The purpose of this study was to evaluate the economic efficacy of a bevacizumab combined with temozolomide + irinotecan regimen for the treatment of recurrent pediatric medulloblastoma in China. Methods: The data analyzed were from a randomized phase II screening trial that showed an improved survival benefit in child patients with recurrent medulloblastoma treated with a T+I+B combination regimen. A Markov model is constructed to estimate the incremental cost–effectiveness ratio (ICER) from the perspective of Chinese society. The uncertainty in the model is solved by one-way certainty and probabilistic sensitivity analysis. Results: Our base case analysis showed that the total costs of treatment increased from 8,786.403 to 27,603.420 with the combination bevacizumab versus the two-agent chemotherapy regimen. Treatment with T+I+B combination therapy was associated with an increase in effectiveness of 0.280 QALYs from 0.867 QALYs for the T+I regimen to 1.147 QALYs T+I regimen. The cost-effectiveness ratio was 67,203.632/QALY, with a 0% probability of being cost-effective at a WTP threshold of 38,136.26/QALY (Figure 2, Table II). Cost changes associated with grade 3-4 AE management, tests used, or hospitalization costs had little effect on the ICER values predicted by sensitivity analysis. Conclusions: Taken together, the results of this study suggest that the combination of bevacizumab with temozolomide and irinotecan is not a cost-effective option from the perspective of Chinese payers as a first-line treatment option for children with recurrent medulloblastoma in China.